1997
DOI: 10.1046/j.1365-2273.1997.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the head and neck

Abstract: Adenoid cystic carcinoma has a long natural history but frequently proves fatal. The present study describes 108 patients with an adenoid cystic carcinoma of the head and neck seen over a 30-year period. Analysis of the data utilized both univariate and multivariate methods. Forty per cent of patients had tumours arising from the oral cavity and half of these were in the hard palate; 29% occurred in the major salivary glands; 41% of tumours were locally advanced at presentation and 11% had lymph node metastase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
3
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 0 publications
3
60
3
2
Order By: Relevance
“…Additionally, we did not find that increased age was associated with increased recurrence rate or overall survival which is in contrast with other study [20]. Jones et al [21] reported that males with primary adenoid cystic carcinomas of the head and neck had a significantly better prognosis than females, while our results indicated that females had a better disease-specific survival. Consistent with other study positive surgical margin was a strong prognostic factor [9].Meanwhile, one study showed the adequacy of surgical resection did not seem to influence overall survival or recurrence rate [16].…”
Section: Discussioncontrasting
confidence: 57%
“…Additionally, we did not find that increased age was associated with increased recurrence rate or overall survival which is in contrast with other study [20]. Jones et al [21] reported that males with primary adenoid cystic carcinomas of the head and neck had a significantly better prognosis than females, while our results indicated that females had a better disease-specific survival. Consistent with other study positive surgical margin was a strong prognostic factor [9].Meanwhile, one study showed the adequacy of surgical resection did not seem to influence overall survival or recurrence rate [16].…”
Section: Discussioncontrasting
confidence: 57%
“…Adenoid cystic carcinoma can occur in any salivary gland, but approximately 50% develop within the minor salivary glands with parotid the most common site of occurrence (11). In the submandibular gland, this tumor accounts for 12% to 17% of all tumors (12). A possibility of tumor was ruled out for this patient because swelling, pain and paresthesia were not constant and a radiopaque nodule was detected in OPG.…”
Section: Discussionmentioning
confidence: 99%
“…Perineural invasion is a typical feature, with high frequency of pain. 17 Salivary duct adenocarcinoma is a rare and highly aggressive tumor with solid, tubular and cribriform patterns, that closely resemble invasive ductal carcinoma of the breast. It is rare high-grade form, aggressive with frequent metastases.…”
Section: Discussionmentioning
confidence: 99%